Shakespeare : A Very Short Introduction - Greer, Germaine (Karachi, Pakistan Oxford University Press, 2007)
A series of concise, engrossing, and enlightening books that explore every subject under the sun with unique insight.
Include Index and Colour Illustration
Keywords: Shakespeare, William, 1564-1616